Expect the unexpected: The dilemmas in the diagnosis and management of interstitial ectopic pregnancy-Case report and literature review - Madhavi Kalidindi; Anupama Shahid; Funlayo Odejinmi (Wolters Kluwer Medknow Publications, 2016)
Interstitial pregnancy is a rare type of ectopic pregnancy; it tends to present late, is most commonly missed, and is associated with significant maternal morbidity and mortality. Early clinical diagnosis aided by ultrasound and laparoscopy may help contribute towards effective conservative or fertility preserving treatment modalities and thereby reduce potential morbidity and mortality. We present a case of missed interstitial pregnancy in an inner city London hospital, where the ultrasound diagnostic accuracy published is as high as 90%, with the aim of analyzing the difficulties and dilemmas in the diagnosis and the management of interstitial pregnancies.